ANALISA PENGULANGAN (REPEAT) CITRA RADIOGRAFI DI UNIT RADIOLOGI RUMAH SAKIT AWAL BROS PANAM PEKANBARU - T.Mohd Yoshandi; Ahmad Sayuti; Marido Bisra (Journal of Hospital Administration and Management, 2020)
Repeat analysis is a systematic process to categorize repeated images and determine the causes of repeat, so that repeat can be minimized or eliminated. Radiology Facility at Awal Bros Panam Pekanbaru Hospital has a repeat percentage of digital images in March to May 2020 of 7.50%, which exceeds the rejection rate limit in the Decree of the Minister of Health Number 129 / Menkes / SK / II / 2008. The purpose of this study was to determine the percentage of repeated digital image along with the repeat factors and the efforts made to decrease the repeat rate. The population in this study were all digital images on Computed Radiography that occurred in March to May 2020. The research sample was the number of digital images which were repeated during March to May 2020. Data obtained from the observation within a span of three months. Data analysis was carried out using a formula to be compared with the tolerance limit set by the Ministry of Health. Quantitative research with a descriptive approach and data collection methods carried out by means of survey. Quantitative research is research that connects or compares one variable to another The resulting data is numerical or numeric has a hypothesis as the initial assumption of research. Data collection is through tests and non-tests, data analysis with statistics measurment, and research results or conclusions can represent population. The results showed the percentage of repeat digital images at the Radiology Facility at Awal Bros Panam Pekanbaru Hospital in March to May 2020 was 7.50%. The repeat factors were patient position (66.5%), patient movement (19.9%), artifact (10.2%), and mechanical exposure factor (4.2%). Solution to decrease the repeat rate were to improve the communication between doctors and patients, to improve the radiographer’s ability, and maintanance and repairment of equipment periodically. The percentage of repeat radiography images at the Radiology Facility of Awal Bros Panam Pekanbaru Hospital in period of March to May 2020 is 7.50% and the factors that cause the repeats were patient position (66.5%), patient movement (19.9%), artefact (10.2%), and mechanical (4.2%).